Labor market risks in times of welfare state transformation - Hanna Schwander (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2015)
This paper is concerned with the link between welfare state reforms and the rising labor market inequality between labor market insiders and outsiders. This labor market inequality represents one of biggest challenges to Europe, especially to Continental Europe. The paper starts with a review of the most important labor market and welfare state reforms in Germany, France, Italy and Spain, four continental European countries with strong insider-outsider divides. I then study the implications of welfare state reforms on labor market risks in Continental Europe, focusing on the risk for unemployment and temporary employment because these two forms of labor market risks have particularly strong effects on economic and social deprivation and are often linked to a permanently inferior labor market status. Relying on several waves from the EU-SILC (2005-2011) I examine patterns of labor market risks and their distribution between groups with different skill and age levels and the interaction of these two factors in four Continental European countries: Germany, France, Italy and Spain. The analysis reveals that the development of unemployment and temporary employment varies between the four countries. In Germany, labor market risks have become less unequally distributed since the implementation of the Agenda 2010 in 2005 while labor market inequality has remained constant in France. I relate this back to the rigid labor market and the lack of more than superficial labor market reforms in the last decade until very recently. Indeed, France is a case where we observe a clear effect of a non-event mostly at the cost of the younger generation, which is clearly confronted with higher labor market risks than individuals in their prime age of even elderly individuals. Consistent with the politics of 'selective flexibilization', we find pronounced levels of labor market inequality in Italy and Spain, which are only to increase over time. One might speak of a dualization of the Italian and Spanish labor market between young outsiders and older insiders. – – In diesem Artikel wird der Zusammenhang zwischen Wohlfahrtsstaatsreformen und der steigenden Ungleichheit im Arbeitsmarkt in vier kontinentaleuropäischen Ländern (Deutschland, Frankreich, Italien und Spanien), in welchen die ungleiche Verteilung von Arbeitsmarktrisiken eine besondere Herausforderung darstellt, analysiert. Das Papier beginnt mit einem Überblick über die wichtigsten Arbeitsmarkt- und Sozialstaatsreformen in Deutschland, Frankreich, Italien und Spanien in den letzten 2 Jahrzehnten um dann die Auswirkungen dieser Reformen auf Arbeitsmarktungleichheit zu untersuchen. Der Fokus der Untersuchung liegt dabei auf dem Risiko für Arbeitslosigkeit und dem Risiko für befristete Beschäftigung, zwei Arbeitsmarktrisiken mit schwerwiegenden Auswirkungen auf die soziale und ökonomische Integration der Betroffenen, welche zudem oftmals mit einem dauerhaft Verminderung des Arbeitsmarktstatus verbunden ist. Anhand mehrerer Wellen des EU-SILC (2005-2011) wird die Verteilung von Arbeitsmarktrisiken zwischen Gruppen mit unterschiedlichen Qualifikationen und Altersstufen und das Zusammenspiel dieser beiden Risikofaktoren untersucht. Die Analyse zeigt, dass die Entwicklung der Arbeitsmarktrisiken zwischen den vier Ländern unterschiedlich verläuft. In Deutschland hat sich die Ungleichheit im Arbeitsmarkt aufgrund der Agenda 2010 seit 2005 reduziert, während das Risiko für Arbeitslosigkeit und befristete Beschäftigung in Frankreich konstant ungleich verteilt geblieben ist. Dies kann mit dem starren Arbeitsmarkt und dem Fehlen von tiefgreifenden Arbeitsmarktreformen erklärt werden. Frankreich demonstriert damit, dass auch "Nicht-Ereignisse" deutliche Auswirkungen auf Ungleichheit haben können: Das Festhalten an bestehenden Strukturen ging auf Kosten der jüngeren Generation, die deutlich höheren Arbeitsmarktrisiken ausgesetzt sind als ältere Individuen. Eine ausgeprägte und steigende Ungleichheit in Italien und Spanien finden wir im Einklang mit der Reformstrategie der "selektiven Flexibilisierung", auch in Italien und Spanien. Entsprechend kann die Entwicklung in Südeuropa als Dualisierung zwischen jungen Outsidern und älteren Insider bezeichnet werden.
Keywords: 300